The Effect of Fundamental Frequency Contour Similarity on Multi-Talker Listening in Older and Younger Adults - Wasiuk, Peter A.; Lavandier, Mathieu; Buss, Emily; Oleson, Jacob; Calandruccio, Lauren (The Journal of the Acoustical Society of America, 2020)
Older adults with hearing loss have greater difficulty recognizing target speech in multi-talker environments than young adults with normal hearing, especially when target and masker speech streams are perceptually similar. A difference in fundamental frequency (f0) contour depth is an effective stream segregation cue for young adults with normal hearing. This study examined whether older adults with varying degrees of sensorineural hearing loss are able to utilize differences in target/masker f0 contour depth to improve speech recognition in multi-talker listening. Speech recognition thresholds (SRTs) were measured for speech mixtures composed of target/masker streams with flat, normal, and exaggerated speaking styles, in which f0 contour depth systematically varied. Computational modeling estimated differences in energetic masking across listening conditions. Young adults had lower SRTs than older adults; a result that was partially explained by differences in audibility predicted by the model. However, audibility differences did not explain why young adults experienced a benefit from mismatched target/masker f0 contour depth, while in most conditions, older adults did not. Reduced ability to use segregation cues (differences in target/masker f0 contour depth), and deficits grouping speech with variable f0 contours likely contribute to difficulties experienced by older adults in challenging acoustic environments.
Keywords: dept.cmd; peer-reviewed

The Association Between Endotracheal Tube Size and Aspiration (During Flexible Endoscopic Evaluation of Swallowing) in Acute Respiratory Failure Survivors - Krisciunas, Gintas P.; Langmore, Susan E.; Gomez-Taborda, Stephanie; Fink, Daniel; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Scheel, Rebecca; Rubio, Alix C.; Siner, Jonathan M.; Vojnik, Rosemary; Warner, Heather; et al. (Critical Care Medicine, 2020)
Objectives: To determine whether a modifiable risk factor, endotracheal tube size, is associated with the diagnosis of postextubation aspiration in survivors of acute respiratory failure. Design: Prospective cohort study. Setting: ICUs at four academic tertiary care medical centers. Patients: Two hundred ten patients who were at least 18 years old, admitted to an ICU, and mechanically ventilated with an endotracheal tube for longer than 48 hours were enrolled. Interventions: Within 72 hours of extubation, all patients received a flexible endoscopic evaluation of swallowing examination that entailed administration of ice, thin liquid, thick liquid, puree, and cracker boluses. Patient demographics, treatment variables, and hospital outcomes were abstracted from the patient's medical records. Endotracheal tube size was independently selected by the patient's treating physicians. Measurements and Main Results: For each flexible endoscopic evaluation of swallowing examination, laryngeal pathology was evaluated, and for each bolus, a Penetration Aspiration Scale score was assigned. Aspiration (Penetration Aspiration Scale score ≥ 6) was further categorized into nonsilent aspiration (Penetration Aspiration Scale score = 6 or 7) and silent aspiration (Penetration Aspiration Scale score = 8). One third of patients (n = 68) aspirated (Penetration Aspiration Scale score ≥ 6) on at least one bolus, 13.6% (n = 29) exhibited silent aspiration, and 23.8% (n = 50) exhibited nonsilent aspiration. In a multivariable analysis, endotracheal tube size (≤ 7.5 vs ≥ 8.0) was significantly associated with patients exhibiting any aspiration (Penetration Aspiration Scale score ≥ 6) (p = 0.016; odds ratio = 2.17; 95% CI 1.14-4.13) and with risk of developing laryngeal granulation tissue (p = 0.02). Conclusions: Larger endotracheal tube size was associated with increased risk of aspiration and laryngeal granulation tissue. Using smaller endotracheal tubes may reduce the risk of postextubation aspiration. © 2020 International Anesthesia Research Society.
Keywords: Adult; Aged; Airway extubation; Deglutition; Deglutition disorders; Female; Humans; Intensive Care Units; Intratracheal intubation; Intubation, Intratracheal; Male; Middle Aged; Prospective Studies; Respiration, Artificial; Respiratory Aspiration; Respiratory Insufficiency; Respiratory aspiration; Respiratory distress syndrome; Risk Factors; Survivors; acid aspiration; adverse event; aged; artificial ventilation; clinical trial; dept.cmd; devices; endotracheal intubation; female; human; intensive care unit; male; middle aged; multicenter study; peer-reviewed; physiology; procedures; prospective study; respiratory failure; risk factor; survivor; swallowing

Development of an Accurate Bedside Swallowing Evaluation Decision Tree Algorithm for Detecting Aspiration in Acute Respiratory Failure Survivors - Moss, Marc; White, S. David; Warner, Heather; Dvorkin, Daniel; Fink, Daniel; Gomez-Taborda, Stephanie; Higgins, Carrie; Krisciunas, Gintas P.; Levitt, Joseph E.; McKeehan, Jeffrey; McNally, Edel; Rubio, Alix; et al. (Chest, 2020)
Background: The bedside swallowing evaluation (BSE) is an assessment of swallowing function and airway safety during swallowing. After extubation, the BSE often is used to identify the risk of aspiration in acute respiratory failure (ARF) survivors. Research Question: We conducted a multicenter prospective study of ARF survivors to determine the accuracy of the BSE and to develop a decision tree algorithm to identify aspiration risk. Study Design and Methods: Patients extubated after ≥ 48 hours of mechanical ventilation were eligible. Study procedures included the BSE followed by a gold standard evaluation, the flexible endoscopic evaluation of swallowing (FEES). Results: Overall, 213 patients were included in the final analysis. Median time from extubation to BSE was 25 hours (interquartile range, 21-45 hours). The FEES was completed 1 hour after the BSE (interquartile range, 0.5-2 hours). A total of 33% (70/213; 95% CI, 26.6%-39.2%) of patients aspirated on at least one FEES bolus consistency test. Thin liquids were the most commonly aspirated consistency: 27% (54/197; 95% CI, 21%-34%). The BSE detected any aspiration with an accuracy of 52% (95% CI, 45%-58%), a sensitivity of 83% (95% CI, 74%-92%), and negative predictive value (NPV) of 81% (95% CI, 72%-91%). Using recursive partitioning analyses, a five-variable BSE-based decision tree algorithm was developed that improved the detection of aspiration with an accuracy of 81% (95% CI, 75%-87%), sensitivity of 95% (95% CI, 90%-98%), and NPV of 97% (95% CI, 95%-99%). Interpretation: The BSE demonstrates variable accuracy to identify patients at high risk for aspiration. Our decision tree algorithm may enhance the BSE and may be used to identify patients at high risk for aspiration, yet requires further validation. Trial Registry: ClinicalTrials.gov; No.: NCT02363686; URL: www.clinicaltrials.gov; © 2020 American College of Chest Physicians
Keywords: Airway Extubation; Algorithms; Article; Decision Trees; Deglutition; Female; Humans; Male; Point-of-Care Testing; Predictive Value of Tests; Reproducibility of Results; Respiration, Artificial; Respiratory Aspiration; Respiratory Insufficiency; Risk Assessment; Survivors; Symptom Assessment; United States; acid aspiration; acute respiratory failure; adult; adverse event; aged; algorithm; artificial ventilation; aspiration; bedside swallowing evaluation; clinical trial; controlled study; decision tree; dept.cmd; diagnostic accuracy; diagnostic test accuracy study; digestive system examination; dysphagia; epidemiology; extubation; female; flexible endoscopic evaluation of swallowing; gastrointestinal endoscopy; high risk patient; human; intubation; major clinical study; male; multicenter study; oxygen; oxygen therapy; pathophysiology; peer-reviewed; point of care testing; predictive value; priority journal; procedures; prospective study; pulmonary aspiration; reproducibility; respiratory failure; risk assessment; sensitivity and specificity; speech language pathologist; survivor; swallowing; symptom assessment

Transdisciplinary Approach Practicum for Speech-Language Pathology and Special Education Graduate Students - Weiss, Deborah; Cook, Barbara; Eren, Ruth (Journal of Autism and Developmental Disorders, 2020)
Speech-language pathology and special education graduate student teams participated in an intensive summer practicum for social communication skills with children with autism spectrum disorders, utilizing a transdisciplinary approach that aligned to the frameworks utilized for implementation science. Questionnaires measuring transdisciplinary approach knowledge and comfort level were administered pre/post-practicum. Results of the questionnaires, written daily team reflections, course evaluations, and a focus group interview indicated an increase in all measures, including an increased knowledge of TA, increased understanding and comfort level with the other discipline, and a higher level of confidence and openness in working collaboratively utilizing a transdisciplinary approach. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Academic Performance; Article; Autism Spectrum Disorder; Autism spectrum disorder; Child; Collaborative teaming; Communication; Education, Special; Female; Humans; Implementation science; Interdisciplinary Research; Interprofessional collaboration; Male; Special education; Speech-Language Pathology; Speech-language pathology; Students, Health Occupations; Surveys and Questionnaires; Transdisciplinary; academic achievement; autism; child; comfort; communication skill; course evaluation; dept.cmd; dept.sed; education; female; graduate student; health student; human; implementation science; interdisciplinary education; interdisciplinary research; interpersonal communication; interview; knowledge; male; peer-reviewed; pretest posttest design; priority journal; procedures; professional development; psychology; quantitative analysis; questionnaire; social competence; special education; speech disorder; teacher; training

Abnormalities of Aspiration and Swallowing Function in Survivors of Acute Respiratory Failure - Langmore, Susan E.; Krisciunas, Gintas P.; Warner, Heather; White, S. David; Dvorkin, Daniel; Fink, Daniel; McNally, Edel; Scheel, Rebecca; Higgins, Carrie; Levitt, Joseph E.; McKeehan, Jeffrey; Deane, Sandra; et al. (Dysphagia, 2020)
The mechanisms responsible for aspiration are relatively unknown in patients recovering from acute respiratory failure (ARF) who required mechanical ventilation. Though many conditions may contribute to swallowing dysfunction, alterations in laryngeal structure and swallowing function likely play a role in the development of aspiration. At four university-based tertiary medical centers, we conducted a prospective cohort study of ARF patients who required intensive care and mechanical ventilation for at least 48 h. Within 72 h after extubation, a Fiberoptic Flexible Endoscopic Evaluation of Swallowing (FEES) examination was performed. Univariate and multivariable analyses examined the relationship between laryngeal structure and swallowing function abnormalities. Aspiration was the primary outcome, defined as a Penetration- Aspiration Scale (PAS) score of 6 or greater. Two other salient signs of dysphagia—spillage and residue—were secondary outcomes. A total of 213 patients were included in the final analysis. Aspiration was detected in 70 patients (33%) on at least one bolus. The most commonly aspirated consistency was thin liquids (27%). In univariate analyses, several abnormalities in laryngeal anatomy and structural movement were significantly associated with aspiration, spillage, and residue. In a multivariable analysis, the only variables that remained significant with aspiration were pharyngeal weakness (Odds ratio = 2.57, 95%CI = 1.16–5.84, p = 0.019) and upper airway edema (Odds ratio = 3.24, 95%CI = 1.44–7.66, p = 0.004). These results demonstrated that dysphagia in ARF survivors is multifactorial and characterized by both anatomic and physiologic abnormalities. These findings may have important implications for the development of novel interventions to treat dysphagia in ARF survivors. Clinical Trials Registration ClinicalTrials.gov Identifier: NCT02363686, Aspiration in Acute Respiratory FailureSurvivors. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Deglutition; Deglutition Disorders; Humans; Prospective Studies; Respiratory Aspiration; Respiratory Insufficiency; Survivors; acid aspiration; dept.cmd; dysphagia; human; peer-reviewed; prospective study; respiratory failure; survivor; swallowing

Babysitter training guide for families with individuals with ASD - Bean, K; Neers, K; Cook, Barbara; Eren, R (Encyclopedia of Autism Spectrum Disorders, 2020)
The Second Edition of this major reference work expands its coverage and continues to break new ground as an electronic resource for students, educators, researchers, and professionals. Comprehensive in breath and textbook in depth, the Second Edition of the Encyclopedia of Autism Spectrum Disorders serves as a reference repository of knowledge in the field as well as a regularly updated conduit of new knowledge long before such information trickles down from research to standard textbooks. The Second Edition of the Encyclopedia digests and presents new and updated information for readers who need to stay current with the latest research and clinical practices, including advances in neurobiology and genetics, diagnostic instruments and assessment tests, pharmaceutical treatments, and behavioral, speech and language, and other rehabilitative therapies. The Second Edition of the Encyclopedia covers topics across the following major conceptual areas of ASD and PDDs, including: Research trends and findings Behavior/speech Communication TreatmentsEducation Taking advantage of the techniques offered by the electronic medium, the Second Edition of the Encyclopedia of Autism Spectrum Disorders offers an extensive cross-referencing system facilitating search and retrieval of information. This unique, comprehensive Second Edition of the Encyclopedia of Autism Spectrum Disorders is an essential reference for advanced undergraduate and graduate students as well as researchers, professors, clinicians, and other practitioners across such related disciplines as developmental psychology, child and adolescent psychiatry, social work, child and school psychology, behavioral therapy, and sociology of education.
Keywords: dept.cmd